The Dual Role of VEGF-Mediated Angiogenesis in Oral Tissues: From Physiological Wound Healing to Oral Cancer Progression - Nuroh Najmi; Faisal Kuswandani; Anggun Rafisa; Falisha Febriane Balafif (Jurnal EduHealth, 2026)
Vascular endothelial growth factor (VEGF) is a key regulator of angiogenesis that plays an essential role in maintaining tissue homeostasis and vascular remodeling. In oral tissues, VEGF-mediated angiogenesis is indispensable for physiological wound healing by promoting neovascularization, oxygen delivery, and tissue regeneration. However, dysregulated VEGF signaling also contributes to pathological angiogenesis that supports oral squamous cell carcinoma (OSCC) progression. Understanding these context-dependent functions is essential for developing regenerative and therapeutic strategies targeting VEGF. This narrative review aimed to critically evaluate the dual role of VEGF-mediated angiogenesis in oral tissues by comparing its physiological function during oral mucosal wound healing with its pathological role in oral cancer progression. A narrative review was conducted by synthesizing peer-reviewed literature. Relevant articles were identified using electronic databases with keywords related to oral mucosal wound healing, angiogenesis, VEGF, HIF-1α, oral squamous cell carcinoma, and tumor angiogenesis. Selected studies were analyzed qualitatively to identify the molecular mechanisms regulating VEGF signaling in physiological and pathological conditions.  The reviewed literature demonstrated that transient VEGF activation is essential for physiological angiogenesis, facilitating endothelial cell proliferation, vascular remodeling, and tissue regeneration during oral wound healing. In contrast, persistent VEGF overexpression under chronic hypoxia and inflammation promotes pathological angiogenesis characterized by abnormal vascularization, increased tumor growth, invasion, lymph node metastasis, and poor prognosis in OSCC. Most available studies focused on VEGF in oral cancer, whereas evidence regarding its regulatory role during oral mucosal wound healing remains comparatively limited. VEGF serves as a context-dependent regulator of angiogenesis in oral tissues, contributing to both physiological tissue repair and pathological vascular remodeling. During oral mucosal wound healing, controlled and transient VEGF activation supports neovascularization and tissue regeneration, whereas sustained VEGF signaling under pathological conditions has been associated with angiogenesis that may facilitate oral cancer progression. The current evidence highlights the importance of understanding the molecular regulation of VEGF across different biological contexts. Further studies are needed to clarify the mechanisms governing VEGF activity during oral mucosal wound healing and to explore strategies that promote physiological angiogenesis while maintaining vascular homeostasis and reducing the risk of pathological angiogenesis.